Absence or invisibility? - Carter, Stephen; Dalland, Magnar; Long, Deborah (Scottish Archaeological Internet Reports, 2005)
The modest nature of the archaeological record for Arisaig inevitably raises the question of whether this reflects a genuine scarcity of simply a problem of visibility. The clustering of recorded archaeological sites correlates with what is currently the better archaeological land so it seems reasonable to propose that there is a real focus of past settlement around the current village of Arisaig. Moving out from this core area into what is currently bog or very rocky grazing land it is reasonable to propose that the absence of archaeological sites is real.